Epidemiology, co-infection, and seasonal patterns of respiratory tract infections in a tertiary care center in Saudi Arabia between 2021 and 2022 - Alzahrani, Nabeel; Alshehri, Ahmed; Alshehri, Ali; Al Johani, Sameera (Frontiers in Public Health, 2025)
ObjectivesTo investigate the etiology and epidemiological trends of respiratory tract infections (RTIs) during the COVID-19 pandemic in Saudi Arabia, focusing on age and seasonality.MethodsWe conducted a retrospective analysis of 19,509 respiratory specimens collected from January 2021 to December 2022 at King Abdulaziz Medical City, Riyadh, using the BioFire Filmarray Respiratory Panel 2.1 plus kit.ResultsOf the analyzed specimens, 53.3% (10,406) tested positive for at least one pathogen. Pediatric patients represented 72.5% of positive cases. Rhinovirus/enterovirus (32%) was the most prevalent, followed by SARS-CoV-2 (16%), respiratory syncytial virus (RSV; 13%), and adenovirus (10%).ConclusionsThe study underscores the significant seasonality and age-specific prevalence of RTIs, with winter peaks and a high incidence of rhinovirus/enterovirus, SARS-CoV-2, RSV, and adenovirus. These results emphasize the necessity of ongoing surveillance and targeted public health interventions to manage RTIs effectively.